Identifying the key sludge properties characteristics in Fe2+-activated persulfate conditioning for dewaterability amelioration and engineering implementation. (15th October 2021) - Ge, Dongdong; Zhu, Yidan; Li, Guobiao; Yuan, Haiping; Zhu, Nanwen
Abstract: Fe 2+ -activated persulfate process has been introduced into sludge conditioning currently, however the key sludge properties characteristics are worthwhile comprehensively considering for the engineering implementation and management. The results indicated that both the optimal dosages of persulfate and Fe 2+ were 0.6 mmol/gTS for sludge dewaterability amelioration, and the reduction efficiencies of capillary suction time (CST), specific resistance of filtration (SRF), and water content (Wc) of dewatered sludge cake reached to 90.5%, 97.2%, and 22.4%, respectively. Significantly, the persulfate and Fe 2+ exerted distinctive roles in the conditioning process. The increased persulfate could promote the oxidatively disintegrated effect on sludge flocs, rendering the decrease of particle size. With the oxidative decomposition of the negatively charged biopolymers, sludge zeta potential rose gradually. However, Fe 2+ contributed to more persulfate activation to generate free radicals, and the produced Fe 3+ could further electrically neutralize the broken sludge fragments. The core mechanism of Fe 2+ -activated persulfate conditioning is "destroying and re-building" of sludge flocs. Noteworthily, EPS protein was oxidatively degraded more preferentially than EPS polysaccharide, and the decrease of the α-helix content of EPS protein was conducive to the enhancement of sludge dewaterability. Furthermore, the hydrophilic functional groups reduced clearly and element chemical states on sludge flocs altered pronouncedly, also the destroyed structure and microchannel facilitated the flowability of water. These findings provide theoretical and technical support for the practical engineering implementation of the Fe 2+ -activated persulfate conditioning process. Graphical abstract: Image 1 Highlights: Key sludge properties characteristics were identified comprehensively. Extracellular protein was more preferentially degraded than polysaccharide. The decrease in α-helix content of EPS protein facilitates sludge dewatering. Destroying and re-building of sludge flocs is the core conditioning mechanism.